2006
DOI: 10.1152/ajpcell.00616.2005
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular release of HMGB1 during apoptotic cell death

Abstract: High mobility group box 1 protein (HMGB1) is a non-histone nuclear protein with dual function. Inside the cell, HMGB1 binds DNA and regulates transcription, whereas outside the cell, it serves as a cytokine and mediates the late effects of LPS. The movement of HMGB1 into the extracellular space has been demonstrated for macrophages stimulated with LPS as well as cells undergoing necrosis but not apoptosis. The differential release of HMGB1 during death processes could reflect the structure of chromatin in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
357
1
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 473 publications
(389 citation statements)
references
References 50 publications
19
357
1
12
Order By: Relevance
“…However, HMGB1 release from apoptotic cells has also been reported, including from staurosporine-treated Jurkat, U937 and HeLa cells. 27 Although apoptotic cardiomyocytic and neuronal cells also released in vitro moderate doses of HMGB1 in this study, these failed to attract monocytes or iDC, whereas HMGB1 from necrotic cells or recombinant HMGB1 did. This may be due to a dose effect.…”
Section: Migration Of Msc Towards Recombinant Hgf Was Inhibitedmentioning
confidence: 50%
See 1 more Smart Citation
“…However, HMGB1 release from apoptotic cells has also been reported, including from staurosporine-treated Jurkat, U937 and HeLa cells. 27 Although apoptotic cardiomyocytic and neuronal cells also released in vitro moderate doses of HMGB1 in this study, these failed to attract monocytes or iDC, whereas HMGB1 from necrotic cells or recombinant HMGB1 did. This may be due to a dose effect.…”
Section: Migration Of Msc Towards Recombinant Hgf Was Inhibitedmentioning
confidence: 50%
“…[23][24][25] Moreover, HMGB1 is a prototypic damageassociated molecular pattern passively released from necrotic cells. 26 Although it may be released from apoptotic cells as well, 27 it appears to be preferentially retained in apoptotic bodies because of enhanced chromatin binding 26 and to be inactive due to oxidization of the crucial cysteine residues 23, 45 and 106, 28,29 which is critical for the tolerogenic nature of apoptotic cell death. Either secreted or passively released from necrotic cells, HMGB1 exerts its effects via the receptor of advanced glycation end products (RAGE) 30 and the tolllike receptors TLR-2 and TLR-4, 31 and may form complexes with chemokines-such as chemokine C-X-C motif ligand 12 (CXCL12), enhancing their activity.…”
mentioning
confidence: 99%
“…Although HMGB-1 is regarded as a trigger of these immune/inflammatory disorders mediated via RAGE and TLR and also affects immunological abnormalities [5,6,9,12,23], correlation of serum…”
Section: Serum Levels Of Hmgb-1 and Srage In Sscmentioning
confidence: 99%
“…Although these abnormalities were associated with several organ involvement and systemic vascular damage, the mechanism and pathogenesis of SSc remain unknown [4]. Recent studies have shown that damaged, necrotic, and apoptotic cells release high mobility group box 1 protein (HMGB-1) [5,6]. HMGB-1 is a non-histone nuclear protein with dual function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation